2022
DOI: 10.1002/mdc3.13461
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 and Related Parkinsonism: The Clinical Evidence Thus Far

Abstract: Background The Coronavirus disease 2019 (Covid‐19) pandemic has fueled both research and speculation, as to whether it could be a “perfect storm” for a post‐Covid emergence of parkinsonism in some susceptible individuals, analogous to the post‐encephalitic parkinsonism reported after the 1918 influenza epidemic. This theory is further augmented by reports of a pathogenic effect of the Severe Acute Respiratory Syndrome Coronavirus‐2 (SARS‐CoV‐2) on the central nervous system with specific impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 73 publications
0
22
0
3
Order By: Relevance
“…To date, only few cases of parkinsonism have been reported in literature following COVID-19 infection [ 19 , 20 , 76 , 77 , 78 ]. In these studies, the authors speculate a possible causative link between COVID-19 infection and a post-COVID new-onset parkinsonian phenotype, but they do not address the possibility of prodromal, pre-symptomatic PD, which became symptomatic as a result of biological or psychological stress processes associated with COVID-19.…”
Section: Sars-cov-2 Infection and Pd Overlapsmentioning
confidence: 99%
“…To date, only few cases of parkinsonism have been reported in literature following COVID-19 infection [ 19 , 20 , 76 , 77 , 78 ]. In these studies, the authors speculate a possible causative link between COVID-19 infection and a post-COVID new-onset parkinsonian phenotype, but they do not address the possibility of prodromal, pre-symptomatic PD, which became symptomatic as a result of biological or psychological stress processes associated with COVID-19.…”
Section: Sars-cov-2 Infection and Pd Overlapsmentioning
confidence: 99%
“…Characteristics of patients with new-onset post-COVID-19 parkinsonism(Boura and Chaudhuri 2022) National Institute for Health and Care Excellence in the United Kingdom as signs and symptoms that occur during or after an infection consistent with COVID-19, persisting for more than 12 weeks which are not explained by an alternative diagnosis…”
mentioning
confidence: 99%
“…SARS-CoV-2 could enter the nasal cavity, then the olfactory bulb and the piriform cortex, and finally the brainstem, where the substantia nigra pars compacta is located [ 84 ]. Because the blood–brain barrier is absent in the olfactory bulb, viral entry is made easier [ 14 ]. A recent study revealed that COVID-19 infection was associated with reduced gray matter thickness in the parahippocampal gyrus and orbitofrontal cortex, as well as changes in brain areas with a functional connection to the primary olfactory cortex [ 85 ].…”
Section: Ace2 In Pd and Covid-19: Connecting The Dotsmentioning
confidence: 99%
“…There are some cases of parkinsonism related to COVID-19 that occurred shortly after or concurrently with the infectious disease, representing potential post-viral parkinsonian syndromes. Some of these cases also showed evidence of nigrostriatal pathway deficits in the functional imaging, suggesting potential dopaminergic degeneration [ 14 ].…”
Section: Introductionmentioning
confidence: 99%